FNAC of breast lesions with special reference to IAC standardized reporting and comparative study of cytohistological grading of breast carcinoma - Hemlata Panwar (Journal of Cytology, 2020)
Background: International Academy of Cytology (IAC) has established a process to produce comprehensive and standardized approach to fine-needle aspiration cytology (FNAC) reporting. They have categorized the breast lesions in C1 to C5. (C1-Insufficient material, C2-Benign, C3- Atypical, C4-Suspicious & C5-Malignant). Aims and Objectives: The aim of study is to classify various breast lesions (C1 to C5) and to grade breast carcinoma on FNAC using Robinson's grading system which is then correlated with modified Bloom–Richardson grading. Materials and Methods: All routine FNAC for breast lump were included in the study during the period from Jan 2016 to Jan 2017. The study was conducted in the Department of pathology and lab medicine of a tertiary care hospital in central India. Results: A total 225 female patients were included in the study, with an age group ranging from 15 - 79 years, with lesions in breast were taken. C1 lesions were found in 3 cases, C2 in 186 cases, C3 in 13 cases, C4 in 4 cases, and C5 in 19 cases. Correlation of cytohistological grading was obtained in 108 cases. Conclusion: Cytological categorization based on IAC structured reporting will enhance the reproducibility of reports among pathologist & clinicians. With the comparison between cytohistological nuclear grading, the cytoprognostic scores will help in evaluating the aggressiveness of tumor, predicts histological grade and prognosis. It could be a useful parameter for selecting neo-adjuvant chemotherapy.